2017
DOI: 10.1080/2162402x.2017.1349589
|View full text |Cite
|
Sign up to set email alerts
|

A novel bifunctional anti-PD-L1/TGF-β Trap fusion protein (M7824) efficiently reverts mesenchymalization of human lung cancer cells

Abstract: Mesenchymalization is a cellular and molecular program in which epithelial cells progressively lose their well-differentiated phenotype and adopt mesenchymal characteristics. Tumor mesenchymalization occurs during the progression of cancer to metastatic disease, and is also associated with resistance to multiple therapeutics, including killing by cytotoxic immune cells. Furthermore, tumor cells can evade immune destruction by upregulating the checkpoint molecule PD-L1, and emerging research has found higher PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
130
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 151 publications
(139 citation statements)
references
References 59 publications
1
130
0
1
Order By: Relevance
“…This fusion protein blocked signaling from the immune checkpoint PD-L1 surface protein and decreased TGF-b signaling within the tumor microenvironment by binding all three TGF-b isoforms. Its dual anti-immunosuppressive function resulted in the activation of both the innate and the adaptive immune system, upregulation of tumor cell PD-L1 levels, and the induction of tumor regression in mouse models [69,70]. These encouraging results highlight the centrality of TGF-b signaling in regulation of the antitumor immune response and offer a glimpse of the translational potential of immunotherapeutics targeting TGF-b signaling for HCC.…”
Section: Clinician's Cornermentioning
confidence: 73%
“…This fusion protein blocked signaling from the immune checkpoint PD-L1 surface protein and decreased TGF-b signaling within the tumor microenvironment by binding all three TGF-b isoforms. Its dual anti-immunosuppressive function resulted in the activation of both the innate and the adaptive immune system, upregulation of tumor cell PD-L1 levels, and the induction of tumor regression in mouse models [69,70]. These encouraging results highlight the centrality of TGF-b signaling in regulation of the antitumor immune response and offer a glimpse of the translational potential of immunotherapeutics targeting TGF-b signaling for HCC.…”
Section: Clinician's Cornermentioning
confidence: 73%
“…Compared to anti-PD-L1, bintrafusp alfa was also shown (7) to increase the gene expression of molecules involved in T-cell trafficking in the tumor (e.g., CXCL11), TRAIL-mediated tumor cell lysis, and antigen-specific T-cell lysis of tumor cells. Prior studies (6) have also shown that TGF-β1 serves as a molecular link between human lung tumor cell mesenchymalization and elevated PD-L1 expression and that this mesenchymalization was effectively antagonized using bintrafusp alfa, but not by anti-PD-L1.…”
Section: Introductionmentioning
confidence: 94%
“…Bintrafusp alfa (M7824) is an innovative first-in-class bifunctional fusion protein composed of the extracellular domain of the TGF-βRII to function as a TGF-β "trap" fused to a human IgG1 antibody blocking PD-L1. Several prior studies have been carried out characterizing the biologic activity of bintrafusp alfa both in vitro and in vivo, employing both murine and human immune cells and tumor cells (6)(7)(8)(9)(10). Bintrafusp alfa was shown to be capable of mediating antibody-dependent cell-mediated cytotoxicity (ADCC) for a wide range of human carcinoma cells Abbreviations: β2m, beta-2 microglobulin; CRADA, Cooperative Research and Development Agreement; GvHD, Graft vs.…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing trials of the TGF‐β antibody galunisertib plus nivolumab and durvalumab are being explored in pancreatic cancer, NSCLC, hepatocellular carcinoma, and other solid tumors. Additionally, an extremely promising strategy to target TGF‐β involves using a bispecific antibody against PD‐L1 or CTLA‐4 with a TGF‐β trap . Dramatic responses were observed with this drug in cervical cancers and pancreatic cancers, with an ongoing study including multiple expansion cohorts .…”
Section: Sarcomas—a Framework For Approaching Modern Immunotherapymentioning
confidence: 99%